Analysis of ex vivo drug response data of Plasmodium clinical isolates: the pros and cons of different computer programs and online platforms - Wirjanata, G; Handayuni, I; Zaloumis, SG; Chalfein, F; Prayoga, P; Kenangalem, E; Poespoprodjo, J; Noviyanti, R; Simpson, JA; Price, RN; Marfurt, J (BioMed Central, 2016)
Background In vitro drug susceptibility testing of malaria parasites remains an important component of surveillance for anti-malarial drug resistance. The half-maximal inhibition of growth (IC50) is the most commonly reported parameter expressing drug susceptibility, derived by a variety of statistical approaches, each with its own advantages and disadvantages.